PENGARUH PEMBIAYAAN MURABAHAH, ISTISHNA, MUDHARABAH, DAN MUSYARAKAH TERHADAP PROFITABILITAS (STUDI PADA BANK SYARIAH DI INDONESIA PERIODE MARET 2015 – AGUSTUS 2016) - Sari, Dewi Wulan; Anshori, Mohamad Yusak (JURNAL AKUNTANSI DAN MANAJEMEN, 2017)
This thesis aims to determine how much influence policy-contract agreement the Islamic bank financing (murabahah, istishna, mudharabah, and musyarakah) against the profitability of Islamic banks. Profitability used in this thesis is the Bukopin Syariah, BRI Syariah, BSM, and Muamalat Indonesia Bank. The data in this paper uses secondary data, monthly financial statements (balance sheet and income statement) in the period March 2015-August 2016. The financial statement has been taken from the publication of the report issues by the website of each bank. Mechanical of data management using multiple linear, regression, and test the classical assumption of normality test, multikoloniaritas, heteroksidasitas, and autokorolation, while proving the hypothesis of determination R2, F statistical test, and the test T statistic.